Short-term effects of comprehensive pulmonary rehabilitation and its maintenance in patients with idiopathic pulmonary fibrosis: a randomized controlled trial - Jarosch, Inga; Schneeberger, Tessa; Gloeckl, Rainer; Kreuter, Michael; Frankenberger, Marion; Neurohr, Claus; Prasse, Antje; Freise, Julia; Behr, Juergen; Hitzl, Wolfgang; Koczulla, Andreas R.; Kenn, Klaus (Journal of Clinical Medicine, 2020)
The recommendation for pulmonary rehabilitation (PR) in idiopathic pulmonary fibrosis (IPF) is weak with low-quality evidence. Therefore, the aim of this study is to investigate short-term PR effects and their maintenance after a 3-month follow-up. Fifty-four IPF patients were randomized into a group receiving a 3-week comprehensive, inpatient PR (n = 34, FVC: 74 ± 19% pred.) or usual care (UC) (n = 17, FVC: 72 ± 20%pred.). Outcomes were measured at baseline (T1), after intervention (T2), and 3 months after T2 (T3). A 6-min walk distance (6MWD) was used as the primary outcome and chronic respiratory disease questionnaire (CRQ) scores as the secondary outcome. Change in 6MWD from T1 to T2 (Δ = 61 m, 95% CI (18.5–102.4), p = 0.006) but not from T1 to T3 (∆ = 26 m, 95% CI (8.0–61.5), p = 0.16) differed significantly between groups. Higher baseline FVC and higher anxiety symptoms were significant predictors of better short-term 6MWD improvements. For the change in CRQ total score, a significant between-group difference from T1 to T2 (∆ = 3.0 pts, 95% CI (0.7–5.3), p = 0.01) and from T1 to T3 (∆ = 3.5 pts, 95% CI (1.5–5.4), p = 0.001) was found in favour of the PR group. To conclude, in addition to the short-term benefits, inpatient PR is effective at inducing medium-term quality of life improvements in IPF. PR in the early stages of the disease seems to provoke the best benefits.